Determination of oxygen radical production in spondyloarthropathies by whole blood chemiluminescence. Issue 11 (November 1991) - Ristola, M; Leirisalo-Repo, M; Repo, H
Abstract : Oxygen derived free radicals are considered to play an important part in the development of inflammation. A whole blood chemiluminescence assay was used to study N-formyl-methionyl-leucyl-phenylalanine induced oxygen radical production in subjects with ankylosing spondylitis or previous yersinia arthritis. In luminol enhanced chemiluminescence, the subjects with previous yersinia arthritis showed significantly increased initial activation (at one minute), whereas the subjects with ankylosing spondylitis showed decreased responses at both the initial activation and at peak activation (at two to three minutes). This finding gives credence to the view that, in terms of oxygen radical production, the pathogenesis of yersinia arthritis is different from that of ankylosing spondylitis.